In Vivo Measurements of Middle Ear Temperature During Transcanal Endoscopic Ear Surgery. Issue 8 (19th September 2021) - Beláková, Petra; Salzman, Richard; Hyravý, Martin; Heřman, Jan
Abstract : Objective: The light emitted from the endoscope during transcanal endoscopic ear surgery (TEES) heats the intratympanic space. This heat may potentially be dangerous to nearby important structures, as documented by in vitro and by animal and cadaveric studies. The aim of our work was to monitor middle ear temperatures during TEES in vivo. Study Design: Cohort study. Setting: Tertiary referral hospital. Patients: Four patients (15–69 yrs old) underwent transcanal endoscopic tympanoplasties for chronic perforation or retraction. Intervention: After elevating the tympanomeatal flap, a thermocouple was placed in the middle ear to measure the heat generated by a 30° Hopkins rod telescope (11 cm long, 2.7 mm wide) and fiberoptic light emitting diode light source. Main Outcome Measures: Middle ear temperature in the retrotympanum was monitored under these conditions: at 50 and 100% light intensity, after removing and wiping the endoscope tip, during suctioning and following middle ear irrigation. Results: Maximum middle ear temperature ranged from 36.26–37.30°C. Pulling out and wiping the endoscope caused no change or minimal decrease of 0.16°C. Middle ear irrigation caused a temperature drop of 2.05°C to 5.11°C. Suctioning was associated with a drop from 0.24°C to 3.91°C that was dependent on the depth of the endoscopic tip. Conclusion: Middle ear temperatures during TEES using a Hopkins rod telescope and light-emitting diode light source reach values corresponding to physiological body temperature, and do not reach dangerous levels.